Effects of One Year of Vitamin D and Marine Omega-3 Fatty Acid Supplementation on Biomarkers of Systemic Inflammation in Older US Adults. (4th February 2020) - Costenbader, Karen H; MacFarlane, Lindsey A; Lee, I-Min; Buring, Julie E; Mora, Samia; Bubes, Vadim; Kotler, Gregory; Camargo, Carlos A; Manson, JoAnn E; Cook, Nancy R
Abstract: BACKGROUND: Observational studies suggest vitamin D and marine ω-3 fatty acid (n-3 FA) supplements are associated with lower systemic inflammation. However, past trials have been inconsistent. METHODS: The randomized, double-blind, placebo-controlled VITamin D and OmegA-3 TriaL (VITAL) tested vitamin D (2000 IU/day) and/or n-3 FA (1 g/day) supplementation in a 2 × 2 factorial design among women ≥55 and men ≥50 years of age. We assessed changes in interleukin (IL)-6, tumor necrosis factor receptor 2 (TNFR2), and high-sensitivity C-reactive protein (hsCRP) concentrations from baseline to 1 year among participants randomized to vitamin D + n-3 FA (392), vitamin D (392), n-3 FA (392), or placebo only (385). Geometric means and percent changes were compared, adjusting for baseline factors. RESULTS: Baseline characteristics were well balanced. In the active arms, 25-OH vitamin D rose 39% and n-3 FA rose 55% vs minimal change in placebo arms. Neither supplement reduced biomarkers at 1 year. Vitamin D resulted in 8.2% higher IL-6 (95% CI, 1.5%–15.3%; adjusted P = 0.02), but TNFR2 and hsCRP did not. Among 784 receiving vitamin D, hsCRP increased 35.7% (7.8%–70.9%) in those with low (<20 ng/mL) but not with higher baseline serum 25(OH) vitamin D [0.45% (−8.9% to 10.8%); P interaction = 0.02]. Among 777 randomized to n-3 FA, hsCRP declined [−10.5% (−20.4% to 0.8%)] in those with baseline low (<1.5 servings/week), but not with higher fish intake [6.4% (95% CI, −7.11% to 21.8%); P interaction = 0.06]. CONCLUSIONS: In this large sample from a population-based randomized controlled trial, neither vitamin D nor n-3 FA supplementation over 1 year decreased these biomarkers of inflammation. ClinicalTrials.gov Identifier: NCT01169259; NCT01351805